Three new northern Brazilian Myrtaceae - Sobral, Marcos; Souza, Maria Anália Duarte De; Luize, Bruno G. (Phytotaxa, 2015)
Calyptranthes irregularis, Eugenia abunan and Myrcia macaca are described, illustrated and compared with related species. Calyptranthes irregularis, from the state of Amazonas, is related to C. cuspidata, from which it is distinguished by blades with adaxially sulcate midvein, larger flowers and a calyx with irregular splitting; Eugenia abunan, from the state of Rondônia, is related to E. multirimosa, differing in its larger flowers and absent calyx tube; Myrcia macaca, from the state of Roraima, is related to M. porphyrea and M. crispa, differing mainly by its trilocular ovary.